Low-Frequency Sound Absorption Potential of Subwavelength Absorbers Based on Coupled Micro-Slit Panels - QIAN, Yujie; GAO, Zhengyuan; ZHANG, Jie (Archives of Acoustics, 2024)
Due to space limitations during installation, reducing low-frequency noise has always been a challenging area. Sub-wavelength structures are typically favored in such scenarios for noise reduction. This paper explores the potential of micro-slit panels (MSP) for low-frequency sound absorption. To further optimize the panel thickness, coupled MSPs (CMSP) with a distance between two MSPs of less than 1 mm are proposed. Firstly, the low-frequency absorption performances of a single MSP based on two optimized schemes – the cavity-depth optimal scheme (COS) and the panel thickness optimal scheme (TOS) – are examined and compared with those of existing ultrathin metamaterials. The results demonstrate that MSP has significant potential for low frequency sound absorption, and COS allows for a smaller overall structural thickness but a larger panel thickness than TOS. Secondly, to reduce the panel thickness, the CMSP is developed and the theoretical model of its acoustic impedance is established and validated by experiments. Then, based on the theoretical model, the low-frequency absorption potential of CMSP is optimized using COS. The results show that both the overall thickness and the panel thickness of the CMSP absorber are reduced while maintaining better performance. Furthermore, the proposed absorber achieves a subwavelength scale since its total thickness can be as small as 0.138λ.